A Study of the Correlation Between English Academic Exchanges and Academic Influence - Hong Zhou; Jingyu Xu (SAGE Open, 2025)
To measure the international scholarly impact of researchers and institutions and develop effective predictive models, this study assesses the impact of English-language scholarly exchanges (English-language publication opportunities, international collaborations, and international tenure) on academic impact in non-native English-speaking countries through data analysis. Data were obtained from a database of academic exchanges published by a national research institution in China that focuses on science and engineering research, and the English-language exchange records of 1,889 researchers were statistically analyzed. The guiding research questions aimed to explore the extent to which the subcomponents included in English-language academic exchanges affect academic impact, and the correlations and principal component weights among the components. The statistical results show that the degree and frequency of English academic communication significantly impact influence the academic impact of researchers/institutions. An evaluation model of academic impact based on English academic exchanges (English academic publication opportunities, international academic cooperation, and international academic tenure) was further developed, and the weights and contributions of each influential element were characterized using a normalized evaluation index. The evaluation model is of reference significance for optimizing the evaluation of the academic influence of scholars/research institutes from non-native English-speaking countries and enhancing international exchanges. It further provides necessary solutions for sustainable academic innovation.